Dynamics of the Late Weichselian Svalbard-Barents Sea Ice Sheet and its deglaciation based on high-resolution bathymetric mapping and raised beach records - Minney Sigurðardóttir 1986- (2011)
This thesis aims at giving a literature-based overview of the dynamics of the Late Weichselian Svalbard-Barents Sea Ice Sheet and its deglaciation, based on high-resolution bathymetric mapping and raised beach records. Extensive patterns of large- and medium scale submarine landforms formed by differences in ice-flow regimes are shown by high-resolution bathymetric mapping from the fjords and their adjacent cross-shelf troughs around Svalbard. Mega-scale glacial lineations, lateral moraines and transverse ridges occur superimposed on the fjord, shelf and cross-shelf trough morphology of the margin. From these landforms the ice-flow and dynamics of the last ice sheet over Svalbard can be inferred. The major fjords and their adjacent cross-shelf troughs are interpreted to be the main routes for fast-flowing ice streams draining the ice sheet. Along the west coast of Svalbard, the Bellsund, Isfjorden and Kongsfjorden troughs were major drainage pathways of the ice sheet. On northern Svalbard the main drainage routes were through Woodfjorden and Wijdefjorden-Hinlopen Strait. The pattern of postglacial emergence on Svalbard is important in correlating the timing of the last deglaciation and ice extent and thickness in time and space, along with the submarine landforms. The maximum area of glacier loading is observed on Kongsøya where postglacial raised beaches occur >100 m above sea level. Deglacial unloading began on western and northern Spitsbergen c. 13–12 14C ka ago, and by c. 10.5 14C ka on eastern Svalbard. Ritgerðin dregur saman gögn sem varpa ljósi á virkni jökulhvelsins er huldi Svalbarða og Barentshaf á hámarki síðasta jökulskeiðs, einkum gögn frá hafsbotni umhverfis Svalbarða og strandlínum frá tímanum eftir jöklaleysinguna. Mynstur stórra og meðalstórra neðansjávar landforma sem myndast hafa við mismunandi aðstæður við flæði skriðjökla og ísstrauma frá jökulhvelinu koma fram við neðansjávarkortlagningu fjarða og landgrunns Svalbarða. Stór línuleg landform, jaðargarðar og þverhryggir eru algeng set- ...